Paraoxonase (PON1) polymorphism and activity as the determinants of sensitivity to organophosphates in human subjects - Sirivarasai, Jintana; Kaojarern, Sming; Yoovathaworn, Krongtong; Sura, Thanyachai (Chemico-biological interactions, 2007)
Paraoxonase (PON1) plays an important role in mechanism of organophosphorus compound (OP) toxicity, as seen both in vitro and in vivo studies. Polymorphisms of PON1 gene at coding and promoter regions have also been to affect on the hydrolytic activity and PON1 level. The objectives of this study were to determine PON1 polymorphism and activity in an OP-exposed population and the effects on inhibition of cholinesterase activity. The studied population consisted of control ( n = 30) and exposed groups ( n = 90). All enzyme activities (AChE, BuChE, paraoxonase, arylesterase and diazonase) were measured once for control group and two periods of exposure for exposed group. Three polymorphisms of PON1 (Q192R, L55M and T−108C) were identified only in the exposed subjects. The results demonstrated that AChE activity in both high (345.5 μkat/gHb) and low exposure periods (496.9 μkat/gHb) of the exposed group were significantly different from control group (649.7 μkat/gHb, p < 0.01). For BuChE activity, the exposed group also showed the statistically lower level in both periods (high exposure period: 62.17 μkat/L and low exposure period: 81.84 μkat/L) than those in the control group (93.35 μkat/L). Serum paraoxonase activity was significantly different among individual genotypes, RR > QR > RR, LL > LM and −108CC > −108CT > −108TT, but this was not found for those of arylesterase and diazonase activities. Q192R and L55M as well as Q192R and T−108C also presented substantial linkage disequilibrium. Further analysis was performed with haplotypes and various enzyme activities. AChE activity was not affected by haplotypes. Individuals with “211” haplotype showed significantly higher paraoxonase activity and BuChE activity than other haplotypes but not in diazonase activity. In conclusion, PON1 gene exhibited a wide variation in enzyme activities both within and between genotypes which implied insights of a potentially difference in sensitivity to OP toxicity.